(untitled) (The Pakistan Development Review, 2002)
Pakistan needs to knit itself into global information economy in order to ensure economic development. E-commerce is the essential tool through which this objective can be met. Currently, the economy is in a transition, the span of which needs to be shortened in order to meet the global challenges in the coming years. An institutional approach is essential to develop e-commerce. An appropriate institutional framework will shorten the time span of the transition period and will ensure a smooth transition to information economy. It will provide an effective and efficient use of the existing institutional infrastructure and development of new institutions. It calls for close coordination between the government, industry, and international organisations.